Terrorist Attacks: Do We Know How to Assess the Results? - William J. Manning (The Scientific World Journal)
On September 11, 2001, terrorists destroyed the World Trade Center (WTC) in New York City. Explosions and fires resulted in the complete collapse of the two WTC towers. The collapsing towers served as enormous point sources of gaseous and particulate air pollution, seen as huge plumes of smoke and dust. The smoke contained volatile organic compounds and fine particles and aerosols. The dust fraction contained parts of ceiling tiles, carpets, concrete, adhesives, asbestos, chromium, lead, titanium, and many other elements and materials. Whether there were unusually toxic ingredients in the plumes is largely unknown.